1995
DOI: 10.1007/bf00175729
|View full text |Cite
|
Sign up to set email alerts
|

Ecological constraints on group size: an analysis of spider monkey and chimpanzee subgroups

Abstract: The social organization of spider monkeys (Ateles geoffroyi) and chimpanzees (Pan troglodytes) appear remarkably similar. In this paper, field studies of these two species were used to (1) test a model of ecological constraints on animal group size which suggests that group size is a function of travel costs and (2) assess ecological and social factors underlying the social organization of these two species. Spider monkeys were studied over a 6-year period in Santa Rosa National Park, Costa Rica, and chimpanze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
242
1
10

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(260 citation statements)
references
References 45 publications
7
242
1
10
Order By: Relevance
“…In the 30 years since the term "fission-fusion" was first introduced (Kummer 1971), research in this area has been rather patchy and has focused only on a limited number of topics. For example, significant methodological improvement for the recognition of non-random association patterns has been made (see electronic supplement A), and several socioecological factors influencing party size have been identified (e.g., Chapman et al 1995;Lehmann and Boesch 2004;Mitani, Watts and Lwanga 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 30 years since the term "fission-fusion" was first introduced (Kummer 1971), research in this area has been rather patchy and has focused only on a limited number of topics. For example, significant methodological improvement for the recognition of non-random association patterns has been made (see electronic supplement A), and several socioecological factors influencing party size have been identified (e.g., Chapman et al 1995;Lehmann and Boesch 2004;Mitani, Watts and Lwanga 2002).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the existence of a positive relationship between habitat-wide fruit availability and foraging party size in both spider monkeys and chimpanzees is taken as evidence that resource distribution constrains grouping patterns, and yet resource patch density and distribution explain less than half the variance in party size in these taxa (Chapman et al 1995). In addition, long-term primate studies are increasingly revealing that considerable flexibility in grouping patterns and within-group social relationships may exist both between populations and within the same population of higher FF taxa over time (Strier 2003; see electronic supplement B).…”
Section: Are Higher Ff Taxa "Special"?mentioning
confidence: 99%
“…In such species, party size is positively related to food availability (spider monkey, Ateles paniscus : Symington 1988;Chapman et al 1995; chimpanzee, Pan troglodytes: Isabirye-Basuta 1988; Chapman et al 1995;orangutan, Pongo pygmaeus: Sugardjito et al 1987). Permanently gregarious species, however, should experience variation in expenditure and even net food intake as food supplies vary over time, even though they may respond to increased competition by adjusting the number of individuals using a patch (e.g., mantled howler, Alouatta palliata: Leighton and Leighton 1982;Chapman 1990;vervet, Cercopithecus aethiops: Whitten 1988; long-tailed macaque, Macaca fascicularis: van Schaik and van Noordwijk 1988;baboons, Papio anubis: Barton and Whiten 1993;Thomas langur, Presbytis thomasi: Sterck 1995). Considerable evidence documents the e ect of within-group competition on foraging e ort and some evidence on net food intake in permanently gregarious species (review : Janson 1988: Janson , 1992.…”
Section: Group Living and Predation Riskmentioning
confidence: 99%
“…Group cohesion may be defined using three criteria: stability, coordination and proximity. When group size or within group competition for food increases, dis advantages may outnumber the advantages of group living, (Chapman et al, 1995;Janson and Goldsmith, 1995;Ron et al, 1994). As a consequence, group cohesion decreases and the group may split either temporarily (Kerth et al, 2006;Popa Lisseanu et al, 2008;Wittemyer et al, 2005) or irreversibly (Henzi et al, 1997a, b;Lehman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, grooming seldom exceeds 15% of day time activity for most social species (Dunbar, 1991;Lehmann et al, 2007). Some authors have investigated how an individual manages to maintain its social relationships when grooming time is limited but group size or within group competition for food has increased (Chapman et al, 1995;Dunbar, 1992b;Janson and Goldsmith, 1995;Lehmann et al, 2007;Majolo et al, 2008;Pollard and Blumstein, 2008;Ron et al, 1994). Lehmann et al (2007) have suggested that when group size and the number of available partners increase, each individual will have to spend more time grooming until a certain group size for which it is impossible to maintain relationships with all group members (Dunbar, 1992a;Lehmann et al, 2007;Schino et al, 2009).…”
Section: Introductionmentioning
confidence: 99%